2016
DOI: 10.1155/2016/7935101
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Near-Field Mixing in Parallel Dual Round Jets

Abstract: Parallel underexpanded round jets system has been widely used in engineering applications, and the flow field structures are very complex because of the jets interaction. In this paper, we studied the near-field mixing phenomenon in parallel dual underexpanded jets numerically by solving the Reynolds-Averaged Navier-Stokes Equations. The numerical results agree well with experimental data acquired by particle image velocimetry. Similar to plane jets, to some degree, two round jets are deflected towards the dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To capture correct velocity profile wall Yplus should range from 30 to 300. In other words, wall adjacent cell should be located within the log-law layer [29]. Wall Yplus is defined as Eq(18) [20]:…”
Section: Wall Yplus Analysismentioning
confidence: 99%
“…To capture correct velocity profile wall Yplus should range from 30 to 300. In other words, wall adjacent cell should be located within the log-law layer [29]. Wall Yplus is defined as Eq(18) [20]:…”
Section: Wall Yplus Analysismentioning
confidence: 99%
“…The aim of this study is to investigate numerically the effect of surface curvature when placing different solids bodies between the two parallel jets. The Fluent software was used to solve the governing dynamic equations, due to its efficiency to provide reasonable solutions in many earlier studies [17][18][19][20]. Turbulent velocities and turbulent fields were examined and compared with the configuration without obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several experimental investigations were conducted on twin jets and multijets such as those performed by Okamoto et al (1985), Harima et al (2005), Tadatomo et al (1995), Meslem et al (2011), Rathakrishnan et al (1989), Buchlin, J. M. (2011), Yin et al (2007), Sabareesh (2015), Zheng et al (2016) and Bentarzi et al (2018). Rathakrishnan et al (1989) have shown that two identical jets completely merge at a distance of 30 diameters downstream their exits.…”
mentioning
confidence: 99%